RELATIONAL EGALITARIANISM AND THE GROUNDS OF ENTITLEMENTS TO HEALTHCARE - Berkey, Brian (Les ateliers de l'éthique / The Ethics Forum, 2018)
In recent years, a number of philosophers have argued that much theorizing about the value of equality, and about justice more generally, has focused unduly on distributive issues and neglected the importance of egalitarian social relationships. As a result, relational egalitarian views, according to which the value of egalitarian social relations provides the grounds of the commitment that we ought to have to equality, have gained prominence as alternatives to more fundamentally distributive accounts of the basis of egalitarianism, and of justice-based entitlements. In this paper, I will suggest that reflecting on the kind of explanation of a certain class of our justice-based entitlements that relational egalitarian considerations can offer raises doubts about the project, endorsed by at least some relational egalitarians, of attempting to ground all entitlements of justice in the value of egalitarian social relationships. I will use the entitlement to healthcare provision as my central example. The central claim that I will defend is that even if relational egalitarian accounts can avoid implausible implications regarding the extension of justice-based entitlements to health care, it is more difficult to see how they can avoid what seem to me to be implausible explanations of why individuals have the justice-based entitlements that they do. To the extent that I am correct that relational egalitarian views are committed to offering implausible explanations of the grounds of justice-based entitlements to healthcare, this seems to me to provide at least some support for a more fundamentally distributive approach to thinking about justice in healthcare provision.